Experimental Study on Net Flow Rate Generation Inside Closed Loop Mechanical Circulatory System Using Impedance Pump - Abd Razak, Azli; Izzati Rosli, Nazirul; Faizal Mohamad, Mohd (International Journal of Engineering and Technology, 2018)
This present study focused on the performance of net flow rate inside closed loop mechanical circulatory system with single and double pinching impedance pumps which generates a unidirectional flow of fluid around closed loop of soft viscoelastic tubing. The experimental setup consisted of viscoelastic tubing connected between two ends of rigid tube which was compressed rhythmically or squeezed asymmetrically at various frequencies by motorized pinching. Hence, net flow of fluid around the tubing can occur without valves. Experiment was done on two different fluid, namely Newtonian and Non-Newtonian. Result showed that the flow rate inside closed loop system for non-Newtonian fluid and Newtonian fluid were in good agreement with each other. Single pinching showed a lower flow rate compared to double pinching at higher frequency. The results could be used as a model for a new Mechanical Circulatory Support System used by cardiac patients. Factors influencing the performance of valveless impedance pump was also explained.Â Â